Curriculum Management Improving the Quality of Learning at State Islamic Senior High School in Binjai City - Wan Anwar Fuadi; Neliwati Neliwati; Abdul Halim; Rina Hidayah Tambusai (Edumaspul: Jurnal Pendidikan, 2024)
Curriculum in education is one of the key factors determining the success of education. The curriculum also serves as the brain of an educational institution. With the curriculum, programs can be created and offered to the public, which are useful for the personal development of the students at the institution. A curriculum is a system that has interconnected components in the implementation of education. The curriculum itself must be known and understood by both educators and prospective educators. Quality improvement is a crucial aspect, as the input, process, and output from schools will be under public scrutiny. Therefore, improving the quality of education, particularly in learning, becomes the school's effort to achieve educational goals. This is also the case for Madrasah schools, which are educational institutions in Indonesia capable of competing with other general schools. MAN Binjai, which has been accredited A, is a choice for many parents as a continuing school for their children. Additionally, at MAN Binjai, there are many intra- and extracurricular programs that can encourage students to develop their potential. There are many class programs or majors offered that can be chosen according to the abilities of each participant, as well as facilities that support all learning activities, which can be evidence that MAN Binjai is improving the quality of education. The learning provided also proves to parents and the community who may still have doubts about the quality of education in Madrasah, thinking that Madrasah schools only teach religious knowledge. This is evidenced by several achievements attained by MAN Binjai.